Scaling up forage varieties in SIMLESA Ethiopia sites - International Livestock Research Institute (International Livestock Research Institute, 2017)
This film highlights ILRI's work in helping smallholder farmers increase forage production in the Sustainable Intensification of Maize and Legume Systems for Food Security in Eastern and Southern Africa (SIMLESA) Program sites in Ethiopia.